Anxiety Levels and Associated Factors Among Elderly Patients with Cardiovascular Diseases: A Mixed-Methods Study - Lola Felnanda Amri; Heppi Sasmita; Murniati Muchtar (MEDICA (International Medical Scientific Journal), 2026)
The increasing prevalence of cardiovascular diseases among the elderly is often accompanied by psychological problems, particularly anxiety, which may worsen health outcomes and quality of life. However, limited studies have comprehensively explored anxiety levels and their associated factors among elderly patients in primary healthcare settings. This study aimed to assess anxiety levels and identify associated factors among elderly individuals with cardiovascular disorders in the working area of Puskesmas Anak Air, Padang City. A mixed-methods approach with an explanatory sequential design was employed, combining quantitative and qualitative data. The study involved 139 participants in the quantitative phase and eight participants in the qualitative phase. Most participants were aged 60–74 years (87.1%) and female (69.1%). A small proportion had both hypertension and cardiovascular disease (7.2%), while 30.9% experienced moderate anxiety. Qualitative findings revealed that anxiety was mainly triggered by exposure to distressing information, such as news about death, disasters, and conflicts. Participants commonly managed anxiety through distraction techniques, including light physical activity, watching television, and avoidance coping. In conclusion, moderate anxiety is prevalent among elderly individuals with cardiovascular disorders and is influenced by psychosocial factors. These findings highlight the need for appropriate coping strategies and supportive interventions to reduce anxiety and improve the well-being of the elderly.